Effect of Fatigue, Older Age, Higher Body Mass Index, and Female Sex on Disability in Early Rheumatoid Arthritis in the Treatment‐to‐Target Era. Issue 3 (9th February 2018) - Twigg, Sarah; Hensor, Elizabeth M. A.; Freeston, Jane; Tan, Ai Lyn; Emery, Paul; Tennant, Alan; Morgan, Ann W.
Abstract : Objective: To compare disease activity and disability over 2 years in early rheumatoid arthritis (RA) before and after implementation of treat‐to‐target therapy and identify predictors of adverse outcome. Methods: The Yorkshire Early Arthritis Register (YEAR) recruited 725 patients with early RA between 2002 and 2009, treated with a step‐up approach. The Inflammatory Arthritis Continuum study (IACON) recruited cases between 2010 and 2014 and treated to target. A total of 384 IACON cases met 2010 American College of Rheumatology/European League Against Rheumatism criteria. Latent growth curves of change in Disease Activity Score in 28 joints (DAS28) and the Health Assessment Questionnaire (HAQ) were compared between YEAR and IACON. Latent class growth analysis identified trajectories of change. Baseline predictors of trajectories were identified using logistic regression. Results: The mean DAS28 over 2 years was lower in IACON than in YEAR. Latent trajectories of HAQ change in YEAR were high stable (21% of cohort), moderate reducing (35%), and low reducing (44%). Only moderate reducing (66%) and low reducing (34%) were seen in IACON. In both cohorts, female sex and fatigue predicted adverse HAQ trajectories (high stable and moderate reducing). Odds ratios (ORs) for moderate reducing compared to low reducing for women were 2.58 (95% confidence interval [95% CI] 1.69, 4.49) in YEAR and 5.81 (95% CI 2.44, 14.29) in IACON. ORs per centimeter fatigue visual analog score were 1.13 (95% CI 1.07, 1.20) in YEAR and 1.16 (95% CI 1.12, 1.20) in IACON. Conclusion: Treat‐to‐target therapy gave more favorable trajectories of change in DAS28 and HAQ, but adverse HAQ trajectory was more likely in women with greater fatigue, suggesting such patients would benefit from interventions to improve function as well as reduce inflammation.